1996
DOI: 10.1084/jem.184.6.2411
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Inhibits Antigen Uptake and Presentation by Dendritic Cells

Abstract: Ceramides are intramembrane diffusible mediators involved in transducing signals originated from a variety of cell surface receptors. Different adaptive and differentiative cellular responses, including apoptotic cell death, use ceramide-mediated pathways as an essential part of the program. Here, we show that human dendritic cells respond to CD40 ligand, as well as to tumor necrosis factor-α and IL-1β, with intracellular ceramide accumulation, as they are induced to differentiate. Dendritic cells down-modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 31 publications
2
60
1
Order By: Relevance
“…41 Furthermore, increases in endogenous ceramide or the exogenous addition of ceramide have been shown to inhibit antigen uptake and presentation by dendritic cells. 42 Interestingly, p38 and ERK1/2 have been shown to play opposite roles in tumour dormancy versus metastatic growth in breast, prostate, melanoma, and fibrosarcoma cell lines. 43 A high p38:ERK1/2 ratio induces tumour dormancy, whereas a low p38:ERK1/2 ratio supports tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, increases in endogenous ceramide or the exogenous addition of ceramide have been shown to inhibit antigen uptake and presentation by dendritic cells. 42 Interestingly, p38 and ERK1/2 have been shown to play opposite roles in tumour dormancy versus metastatic growth in breast, prostate, melanoma, and fibrosarcoma cell lines. 43 A high p38:ERK1/2 ratio induces tumour dormancy, whereas a low p38:ERK1/2 ratio supports tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an in vitro culture system revealed that DCs originate from CD34 ϩ pluripotent hemopoietic progenitor cells in the bone marrow and cord blood via myeloid lineage cells in human and murine models (7)(8)(9)(10)(11)(12), and some DCs develop from thymic precursors via lymphoid lineage cells in the murine system (13). Previous studies have shown that TNF-␣, IL-1␤, CD40 ligand (CD40L), LPS, and ceramide can promote DC differentiation in vitro, resulting in irreversible morphological, phenotypical, and functional changes, including upregulation of MHC products and adhesion/costimulatory molecules, down-regulation of Ag uptake, and processing capacity, which result in enhanced TC-stimulatory capacity (13)(14)(15)(16)(17)(18).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…Previously, an in vitro culture system revealed that DCs originate from CD34 ϩ pluripotent hemopoietic progenitor cells (HPCs) in the bone marrow (BM) and cord blood via myeloid lineage cells in human and murine models (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), and some DCs develop from thymic precursors via lymphoid lineage cells in murine system (17).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…DCs were generated from PBMCs, as described previously (9,10), with some modifications (36 -38). Briefly, PBMCs were obtained from 30 ml of leukocyte-enriched buffy coat from healthy donors by centrifugation with Ficoll-Hypaque (Pharmacia Fine Chemicals, Uppsala, Sweden), and the light density fraction from the 42.5-50% interface was recovered.…”
Section: In Vitro Generation and Culture Of Human Dcsmentioning
confidence: 99%